Strategi Pemberdayaan Usaha Mikro Kecil Menengah Melalui Aplikasi E-Peken Pada Dinas Koperasi Usaha Kecil dan Menengah dan Perdagangan Kota Surabaya - Mohammad Nauval Dwi Prabowo; Gading Gamaputra (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
Empowerment of micro, small and medium enterprises is the most important effort in encouraging business actors to have the ability and fulfill their needs in order to compete globally and internationally. The Surabaya City Office of Small and Medium Enterprises Cooperatives and Trade helps the recovery of economic actors online through the Economic Empowerment and Economic Resilience Application (E-Peken). The problem in this study is that there is a mismatch between website login access and smartphones, increased access to small businesses is not yet widespread, and the implementation of training and guidance is not according to the timeline. The purpose of this study is to describe, analyze, and explain the Strategy for Empowering Micro, Small and Medium Enterprises through the E-Peken Application. The type of research is descriptive qualitative. Data source collection techniques using purposive sampling. The focus of the research uses business empowerment strategy efforts according to Sjarifuddin which consists of Financial Capability Improvement Strategies, Marketing Development, Human Resource Development, Regulatory and Control Strategies. The results showed that the empowerment of micro, small and medium enterprises through the E-Peken application can help the economic recovery of business actors. In the indicator of the strategy to improve financial capabilities, the Surabaya City Office of Small and Medium Enterprises and Trade Cooperatives only directs business actors to make loans through Bank Jatim, Mandiri Bank, and Rural Banks (BPR). In the Marketing Development indicator, what is done is to appeal to the District and Kelurahan in Surabaya City to make purchases through the E-Peken application. Furthermore, the indicator of Human Resource Development carried out is conducting guidance and training. In the Regulation and Control strategy indicator, namely by joining through the E-Peken application according to applicable requirements. Suggestions that can be given by researchers, namely the E-Peken application in marketing development can be carried out widely through social media such as Facebook, Instagram and Tiktok. Provide training and guidance according to the timeline, as well as updates related to smartphone-based applications.